Prevalence of gonococcal and chlamydial infections among men who have sex with men in sub-Saharan Africa: a systematic review and meta-analysis - Kehinde Charles Mofolorunsho; Vinogrin Dorsamy; Chauntelle Bagwandeen; Nathlee Samantha Abbai (Systematic Reviews)
Abstract Background Men who have sex with men (MSM) are disproportionately affected by sexually transmitted infections (STI) including Neisseria gonorrhoeae (Ng) and Chlamydia trachomatis (Ct). The lack of robust data on STIs among African MSM has limited the development of evidence-based screening strategies. This study aimed at documenting the pooled prevalence of Ng/Ct among MSM in sub-Saharan Africa (SSA). Methods This systematic review was performed according to the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) 2020 guidelines. Relevant articles from the following databases were searched: PubMed, Scopus, ISI Web of Science, and the Directory of Open Access Journals (DOAJ). Eligible studies reported on the prevalence of Ng/Ct among the MSM population in SSA. Publication bias was assessed using the Hoy tool, Doi plot, and LFK ratio. Due to heterogeneity among studies, subgroup analyses were performed using the MetaXL add-on tool for Microsoft Excel. Results Of 525 articles screened, 20 were selected for inclusion. Six were cross-sectional, four had a prospective cohort study design, and one was an epidemiological study. The pooled prevalence of Ng/Ct in MSM was 27% (95% CI, 19–39%), with an I 2 of 98% signifying heterogeneity among the studies. Subgroup analysis by country revealed South Africa had the highest prevalence (38%). Discussion Interpretation The high prevalence of Ng/Ct infection among MSM in SSA is of concern. Limitations Due to limited data available on Ng/Ct prevalence, the true prevalence of SSA and its associated risk factors is uncertain. Conclusion As the first study to systematically review the available literature on STI prevalence among the MSM population in SSA, it showed the burden of Ng/Ct is higher than in other regions, warranting the strengthening of health systems to improve education, testing, and treatment in MSM population. Systematic review registration PROSPERO CRD42022327095.